2021
DOI: 10.1002/er.7578
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of carbon nanotubes/titanium dioxide and study of its effect on the optical, dielectric, and mechanical properties of polyvinyl alcohol/sodium alginate for energy storage devices

Abstract: Summary In this system, the solvent casting technique was used to prepare polymer nanocomposites from the multiwalled carbon nanotubes (MWCNTs)/TiO2 nanoparticles (as nanofiller)‐doped polyvinyl alcohol/sodium alginate (PVA/SA) blend. The modification in the structure of the nanocomposites is proved by the studies of X‐ray diffraction (XRD) and Fourier transform infrared (FTIR) spectra. The transmission electron microscopy (TEM) analysis evidenced that the MWCNTs/TiO2 nanoparticles were incorporated in the PVA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 42 publications
(20 citation statements)
references
References 86 publications
1
19
0
Order By: Relevance
“…Also, this increasing in the values of σ and σ dc suggested that the NPs formed a three-dimensional conductive pathway within the polymeric nanocomposite samples. 2,5,8 Thus, these σ dc results can be indicated that these polymer nanocomposite samples may be considered as a potential candidate for microelectronic devices as flexible polymeric nanodielectric and for the preparation of novel nanocomposite SPEs with the addition of various alkali metal salts. )…”
Section: Electrical Conductivitymentioning
confidence: 72%
See 4 more Smart Citations
“…Also, this increasing in the values of σ and σ dc suggested that the NPs formed a three-dimensional conductive pathway within the polymeric nanocomposite samples. 2,5,8 Thus, these σ dc results can be indicated that these polymer nanocomposite samples may be considered as a potential candidate for microelectronic devices as flexible polymeric nanodielectric and for the preparation of novel nanocomposite SPEs with the addition of various alkali metal salts. )…”
Section: Electrical Conductivitymentioning
confidence: 72%
“…The strength of the peaks was changed with doping indicating greater interactions between the polymeric chains and the NPs. 5,9,18,21,28…”
Section: Ft-ir Spectramentioning
confidence: 99%
See 3 more Smart Citations